2018
DOI: 10.1126/science.aam8419
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement bursts generate canonical gene fusions in bone and soft tissue tumors

Abstract: Sarcomas are cancers of the bone and soft tissue often defined by gene fusions. Ewing sarcoma involves fusions between , a gene encoding an RNA binding protein, and E26 transformation-specific (ETS) transcription factors. We explored how and when fusions arise by studying the whole genomes of Ewing sarcomas. In 52 of 124 (42%) of tumors, the fusion gene arises by a sudden burst of complex, loop-like rearrangements, a process called chromoplexy, rather than by simple reciprocal translocations. These loops alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
140
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(157 citation statements)
references
References 44 publications
10
140
1
6
Order By: Relevance
“…Genetically, the hallmark of EwS are chromosomal translocations generating chimeric proteins through fusion of the EWSR1 (Ewing sarcoma breakpoint region 1) gene to variable members of the ETS (E26 transformation specific) family of transcription factors, in 85% FLI1 (Friend leukemia virus integration 1) [3][4][5] . These EWSR1-ETS fusion oncoproteins act as aberrant transcription factors that promote tumor initiation and progression by massively rewiring the cellular transcriptome and spliceosome 1,6,7 .…”
Section: Main Text Introductionmentioning
confidence: 99%
“…Genetically, the hallmark of EwS are chromosomal translocations generating chimeric proteins through fusion of the EWSR1 (Ewing sarcoma breakpoint region 1) gene to variable members of the ETS (E26 transformation specific) family of transcription factors, in 85% FLI1 (Friend leukemia virus integration 1) [3][4][5] . These EWSR1-ETS fusion oncoproteins act as aberrant transcription factors that promote tumor initiation and progression by massively rewiring the cellular transcriptome and spliceosome 1,6,7 .…”
Section: Main Text Introductionmentioning
confidence: 99%
“…While great advances in treatment of localized disease have been achieved, established therapies still have limited success in advanced stages despite high toxicity 1 . Thus, more specific and in particular less toxic therapies are urgently required.As a genetic hallmark, EwS tumors express chimeric EWSR1-ETS (EwS breakpoint region 1 -E26 transformation specific) fusion oncoproteins generated through fusion of the EWSR1 gene and variable members of the ETS-family of transcription factors (TF), most commonly FLI1 (85% of all cases) 4,5 . Prior studies demonstrated that EWSR1-FLI1 acts as a pioneer transcription factor that massively rewires the tumor transcriptome ultimately promoting the malignant phenotype of EwS 6,7 .…”
mentioning
confidence: 99%
“…Further, loss of CDKN2A and CDKN2B and a rare type 3 EWS‐FLI1 translocation were noted. The mutational burden of this tumor is higher than the average (∼0.5 mutations/Mb) for Ewing tumors, at 2 mutations/Mb.…”
Section: Germline Bard1 Mutations Associated With Pediatric and Adultmentioning
confidence: 69%